Integration of Knowledge and Practice of Nurses’ Primary Health Care Roles in Hospital - Tamang (Thanju), Shakuntala (Journal of Nepal Health Research Council, 2009)
Background: PHC concept was incorporated in nursing curricula (1987) to equip nurses with necessary knowledge and skills to perform their PHC roles. The aim was to investigate the integration of knowledge and practice of nurses' PHC roles as perceived by the nurse and patient and the relationship with its influencing variables. Methods: A descriptive study involved nurses and patients from government and non-government hospitals using a structured questionnaire. Nonparametric statistics, known for their appropriateness for small samples, were used to examine the research questions. Results: Integration of knowledge and practice of nurses' PHC role was positively reflected in hospitals even though most roles practices were in moderate extent and the significant difference in nurses' role practices were experienced by the patients (P <0.001). The nurses' PHC role practice was influenced by supervision (P <0.001) of work and role of motivator, but were not influenced by other variables. Conclusion: Based on the study findings, an increased in knowledge resulted in an increased in PHC role practice. Therefore, good nursing education program is very important for the nurses to practice PHC roles efficiently and effectively in hospital. There is need for nurses to understand and deliver nursing care congruent with patient's perception of quality nursing care. With the regular and facilitative supervision, the nurses will have guidance encouragement, and resources to perform well. Key words: PHC; Clinician; Developmental; Facilitative; Supportive. doi: 10.3126/jnhrc.v6i2.2216 Journal of Nepal Health Research Council Vol. 6, No. 2, 2008, October Page: 111-116